Style of coping with stress and hope for success among the youth attending the Athletic Sports Championships - Minda, Mateusz; Piasecka, Agata (Journal of Education, Health and Sport, 2019)
Introduction and purpose of the work: In Lazarus and Folkman's transactional theory of stress and coping, stress is treated as a relationship between an individual and environment, which is perceived by a person as excessively demanding. It may lead to a loss of sense of well-being if it exceeds the resources available to the individual. One important personal resource for athletes is the hope for success. The aim of the study was to verify the relations between the style of coping with stress and hope for success among students of sports championship schools. Materials and method: The participants of the study were 51 students who do sports aged 16 to 20 years, including 30 women (59%). The mean age was 17.8 years and the standard deviation was 1.16. In this study, the Coping Inventory for Stresfull Situations (CISS) by Endler and Parker in the polish adaptation of Szczepaniak, Strelau and Wrześniewski and the Adult Hope Scale by Snyder in the polish adaptation of Łaguna, Trzebiński and Zięba were used. Results: The research revealed a significant positive correlation between task-oriented coping and the level of hope for success. Gender considerations revealed significant positive correlations between all styles of coping with stress and the level of hope for success in a group of girls, and this also correlated with task-oriented coping style in a group of boys. Conclusions: The obtained results do not allow to form any final conclusions, but they are an important contribution to improving the knowledge of the relations between styles of coping with stress and hope for success, especially among young athletes. An evaluation of the styles of coping with stress may be of great importance for researches and practitioners working with players.